2021
DOI: 10.1152/ajpregu.00225.2020
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of renal afferents in the maintenance of cardiorenal diseases

Abstract: Elevated sympathetic vasomotor activity is a common feature of cardiorenal diseases. Therefore, the sympathetic nervous system is an important therapeutic target, particularly the fibers innervating the kidneys. In fact, renal denervation has been applied clinically and shown promising results in patients with hypertension and chronic kidney disease. However, the underlying mechanisms involved in the cardiorenal protection induced by renal denervation have not yet been fully clarified. This mini-review highlig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…This observation suggests that increasing both amplitude and pulse duration, additional renal axons are recruited. The renal nerve is known to play an important role in cardiovascular homeostasis ( Ricksten et al, 1979 ; Veiga et al, 2021 ), and it contains both efferent sympathetic and afferent sensory axons from the kidney to the dorsal root ganglia, which project centrally to the brain ( Leal et al, 2012 ; Mizuno et al, 2014 ; Pettigrew et al, 2017 ). It has been reported that denervation of the sinoaortic baroreceptors results in an immediate increase in RSNA, HR, and MAP ( Dibona and Jones, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…This observation suggests that increasing both amplitude and pulse duration, additional renal axons are recruited. The renal nerve is known to play an important role in cardiovascular homeostasis ( Ricksten et al, 1979 ; Veiga et al, 2021 ), and it contains both efferent sympathetic and afferent sensory axons from the kidney to the dorsal root ganglia, which project centrally to the brain ( Leal et al, 2012 ; Mizuno et al, 2014 ; Pettigrew et al, 2017 ). It has been reported that denervation of the sinoaortic baroreceptors results in an immediate increase in RSNA, HR, and MAP ( Dibona and Jones, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…One of the golden key players in the scenario of Cardiorenal Syndrome is the elevation of sympathetic vasomotor activity which has made this nervous system as one of the main therapeutic targets of this syndrome (15). Evidence shows that the sympathetic nerve system has a critical role in regulating body homeostasis, especially controlling body fluids and blood pressure (16,17).…”
Section: Renal Denervation As a Therapeutic Approach For Cardiorenal ...mentioning
confidence: 99%
“…Renal IRI leads to the development of cardiac hypertrophy (CH). In many other models, AKI can directly or indirectly induce acute cardiac dysfunction by increasing angiotensin levels (AT1, AT2, and ACE), local and systemic cytokines (TNF-α, ILs, and IFN-γ), arrhythmias, and other components [45,46], such as increasing the presence of local norepinephrine and increasing sympathetic activity [35,47].…”
Section: Neurohumoral Control In Crsmentioning
confidence: 99%
“…In the figure, it is possible to see the therapies involved in the RAAS blockage: AT1 antagonists, ACR blockers, and renin inhibitors Some vasomotor sympathetic activity is a common characteristic of HF [48]. Therefore, the SNS is a relevant therapeutic target [47]. During HF, renal sympathetic nerve activity increases and causes renal norepinephrine accumulation and renin release, which induces renal vasoconstriction that may contribute to CRS.…”
Section: Neurohumoral Control In Crsmentioning
confidence: 99%